ENT300: general guidelines for operational plan (part 2) - Kamaludin, Mohd Ariff; Nik Jaafar, Nik Fazlin Hiryati; Nik Hassan, Nik Fakrulhazri; Ibrahim, Norlaila; Jasni, Nur Syuhada (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2022)
Flow Chart. Incomplete flow chart will influence the overall operation process of a product or service. If the process is not comprehensive and clear, it will create problems especially in identifying the unit number of machine and equipment needed, purchases of raw material, total number of workers and the total production cost.